The 2021 German Federal Election on Social Media: Analysing Electoral Risks Created by Twitter and Facebook - Kübler, Johanne; Sekwenz, Marie Therese; Rachinger, Felicitas; König, Anna; Gsenger, Rita; Pírková, Eliška; Wagner, Ben; Kettemann, Matthias C.; Krennerich, Michael; Ferro, Carolina (Proceedings of the Annual Hawaii International Conference on System Sciences, 2023)
Safeguarding democratic elections is hard. Social media plays a vital role in the discourse around elections and during electoral campaigns. The following article provides an analysis of the 'systemic electoral risks' created by Twitter and Facebook and the mitigation strategies employed by the platforms. It is based on the 2020 proposal by the European Commission for the new Digital Services Act (DSA) in the context of the 2021 German federal elections. This article focuses on Twitter and Facebook and their roles during the German federal elections that took place on 26 September 2021. We analysed three systemic electoral risk categories: 1) the dissemination of illegal content, 2) negative effects on electoral rights, and 3) the influence of disinformation and developed systematic categories for this purpose. In conclusion, we discuss how to respond to these challenges as well as avenues for future research.
CRIS-Team Scopus Importer:2023-04-21
Keywords: disinformation; elections; Germany; illegal content; platform governance; socio-technical systems